Abnormal uterine bleeding in perimenopausal women: sonographic and histopathological correlation and evaluation of uterine endometrium - Modak, Rupali; Pal, Amitrajit; Pal, Amitava; Bose, Kausik (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The objectives of the study was to establish the role of histopathological diagnosis of uterine endometrial lesions in patients of AUB at perimenopausal age and to correlate the transvaginal sonographic (TVS) finding with histopathological examination. Methods: This prospective observational study was carried out over 1 and 1/2 years in the two apex level teaching hospitals in eastern India. A total of 197 women in the age group of 40-49 years and ≥50 years (up to 55 years) who presented with abnormal uterine bleeding were included in the study. After selecting the patient with eligibility criteria in the OPD, detailed clinical history, systemic and gynecological examinations and investigations were done as per proforma. TVS study of endometrial pattern and thickness was measured followed by dilatation and curettage (D and C) and HPE of the endometrial curetting was done. Results: Menorrhagia (44.67%) was the most common clinical finding. Mean endometrial thickness measured by TVS was 7.04±2.11 mm in proliferative phase and 10.25±1.27 mm in the secretory phase. Proliferative endometrium (37.06%) was the most frequent finding in HPE followed by secretory endometrium (20.3%). Hyperplasia of endometrium was noted in 27 cases (100%) at 12-15 mm of endometrial thickness on TVS whereas endometrial hyperplasia with and without atypia and endometrial carcinoma was noted in 25 cases (92.59%) at the same thickness of 12-15 mm of uterine endometrium on HPE. Endometrial hyperplasia and polyp both had sensitivity of 84.21% and 71.43% respectively on TVS as compared with histopathology. Conclusions: Increased endometrial thickness and echo pattern by TVS correlated well with abnormal endometrial tissue histopathology in perimenopausal women with AUB.